Алгоритм розрахунку прогнозного завантаження автомобільних газонаповнювальних станцій у містах - Кузнецов, Олександр (Видавництво Львівської політехніки, 2015)
Grounded using the algorithm of the forecast load CNG stations that can improve the accuracy of their location choice by improving simulation accuracy.
Algorithm of calculation of prognosis load of the motor-car cng stations is in cities